A new program in cooperative research between academia and industry in Korea, involving Centers of Excellence - Ahn, Soon II
Whilst Korea has experienced impressive economic growth, the growth in technology has been comparatively low. To develop university research potential and university-industry research relationships, Centers of Excellence in Science and Engineering have been and are being established in major universities : their first three years' performance and hopes and recommendations for the future are discussed.
In 1989, Korea initiated a new program aimed at fostering university research potentials and building university-industry research relationships. It involves the establishment of Centers of Excellence in major universities in Korea : Science Research Centers (SRCs) and Engineering Research Centers (ERCs). This program has had a major impact on the universities and engineering communities in Korea. It is too early to claim success, but the initial result is encouraging. This article describes the reasons for establishing the Centers of Excellence and the nature, function and current status of the SRC/ERC program. We examine its first three years' performance and evaluation process, and also examine some of problems and issues that arose while SRCs and ERCs were operating for the first three years. Several utopian recommendations are made, based on the results of evaluation for the effective operations that are most likely to succeed.
Keywords: Cooperative research--Korea.